Study of methods for detecting optical markers in the system of human gait and posture analysis - Barkovska, Olesia; Kovalenko, Andriy; Oliinyk, Dmytro; Ruskikh, Oleksandr; Sedlacek, Peter (Національний технічний університет "Харківський політехнічний інститут", 2025)
The study is dedicated to the relevant topic of automated detection of muscle imbalance and postural deformities, which is particularly in demand among patients with orthopedic prostheses and in pediatric orthopedics. The authors propose a portable monitoring system that uses computer vision methods to assess the level of the pelvis, shoulders, and shoulder blades, ensuring the storage of photogrammetric data for subsequent analysis of rehabilitation results. The purpose of the work is to study methods for detecting optical markers on the human body when analyzing gait. The research tasks included conducting an analysis with a justification of the need to study computer graphics methods in the context of photogrammetric systems used in rehabilitation orthopedics; studying the impact of color characteristics of markers on detection accuracy; studying the impact of marker shape on detection accuracy; and analyzing the obtained results. The subject of the study is computer graphics and machine vision methods for detecting markers on the subject's body. The object of the study is photogrammetric technologies in orthopedics.

Робота присвячена актуальній темі автоматизованого виявлення м’язового дисбалансу та викривлення постави, що є особливо затребуваним серед ортопротезованих пацієнтів та в дитячій ортопедії. Авторами запропонована портативна моніторингова система, яка використовує методи комп'ютерного зору для оцінки рівня тазу, плечей та лопаток, забезпечує зберігання фотограмметричних даних для подальшого аналізу результатів реабілітації. Метою роботи є дослідження методів виявлення оптичних маркерів на тілі людини при аналізу ходи. Задачами дослідження було проведення аналізу із обґрунтуванням затребуваності дослідження методів комп’ютерної графіки в контексті фотограмметричних систем, що використовуються в реабілітаційній ортопедії; дослідження впливу колірних характеристик маркерів на точність іх детектування; дослідження впливу форми маркерів на точність іх детектування; аналіз отриманих результатів. Предметом дослідження є методи комп’ютерної графіки та машинного зору для детектування маркерів на тілі обстежуваного. Об'єктом дослідження є фотограмметричні технології в ортопедії.
Дослідження методів виявлення оптичних маркерів в системі аналізу ходи та постави людини
Keywords: system; дитяча ортопедія; image; spine; baropodometry; anthropometry; модель; система; зображення; дитяча ортопедія; бароподометрія; pediatric orthopedics; дитяча ортопедія; бароподометрія; бароподометрія; бароподометрія